Study on pharmacokinetics and tissue distribution of single dose oral tryptanthrin in Kunming mice by validated reversed-phase high-performance liquid chromatography with ultraviolet detection - Xiaoyan Zhang; Jie Xia; Wenjing Zhang; Yao Luo; Wenbo Sun; Wei Zhou (Integrative Medicine Research)
Background: Tryptanthrin is a major active constituent of several Chinese herbal plants, such as Isatidis radix. Tryptanthrin had been demonstrated to have several beneficial pharmacological effects in vitro for human diseases, including antitumor, anti-inflammatory and antibacteria activities. In contrast to the extensive in vitro investigations, the in vivo disposition process of tryptanthrin was explored limitedly. Methods: In this study, the pharmacokinetics (PK) and tissue distribution of tryptanthrin in Kunming mice following a single oral dose of 80 mg/kg tryptanthrin were investigated for the first time. Mouse plasma, liver, heart, spleen, lung, kidney and brain were collected and analyzed using a validated reversed-phase high-performance liquid chromatography with ultraviolet detection (RP-HPLC–UV) method after biological sample preparation by a simple liquid–liquid extraction. Results: The chromatographic analysis was performed on a Diamonsil C18 column (5 μm, 250 mm × 4.6 mm) and ultraviolet detection was set at a wavelength of 251 nm. The analysis was achieved with a mobile phase of methanol (A) and water (B) (60:40, v/v) at a flow rate of 1.0 mL/min. The method was linear over the concentration range of 4.0–400.0 μg/mL with a lower limit of quantification of 0.10–0.30 μg/mL. Inter- and intraday precisions (relative standard deviations %) were all within 2.93%. Recoveries of tryptanthrin were more than 86.44%. Maximal tryptanthrin concentrations in plasma and tissues of mice were reached within 2.5 hours. The actual highest concentration (Cmax) in mouse plasma was 3.13 μg/mL, the area under the curve (AUC0–t) was 9.38 h μg/mL, and the terminal half-life was 2.27 hours. The volume of distribution was 343.89 mL, the clearance rate was 204.58 mL/h, and the PK of tryptanthrin in mice after oral administration was fit to 2 compartment 1 st Order. After oral dosing of tryptanthrin to Kunming mice, the analyte was well distributed to the plasma and main tissues. Cmax was found in the liver with a mean value of 3.54 μg/g, followed by that in the kidney, lung, spleen, heart, and brain. Conclusion: In this study, a validated RP-HPLC–UV method was developed and successfully applied to PK and tissue distribution of oral tryptanthrin in mice. We confirmed that tryptanthrin was closely related and targeted to plasma, liver, kidney, and lung. These results indicate that tryptanthrin will have a good clinical application in the liver, kidney, or lung. The clinical use of tryptanthrin should focus on its pharmacodynamics and safety study in these tissues.